The role of artificial intelligence (AI) in the development of the educational system of Kurdistan Regional University - محمد, د. مریوان عبدالمجید (Sulaimani Journal for Humanities, 2025)
This study aimed to determine the role of artificial intelligence (AI) in the development of the educational system in Kurdistan Regional Universities, according to age, gender, academic background, university, and teaching experience. Artificial Intelligence (AI) has an impact on the development of teaching methods and student learning in various ways. This study attempts to find the role of (AI) in the development of education systems in public and private universities in Kurdistan Region, (AI). The sample of the study consisted of 47 University Lectures, including Sulaimani, Salahaddin, Duhok, Charmo, Zakho, Raperin, Koya, Halabja, Soran, Garmian, Human Development, Republic. University. The research sample was randomly selected, the questionnaire contains (20) questions, and has a good degree of validity & reliability. In addition, SPSS-26 was used to analyze the data. The results indicated that AI plays a significant role in improving the education system in the Kurdistan Regional Government (KRG) universities. Also, the lecturers' ages were between (30-40) years, and those with teaching experience between (5-10) years, male, lecturers of Sulaimani University, those whose scientific degree was assistant Lecturer could benefit from (47) tools for their classes. Finally, the researcher made some suggestions and recommendations to the Ministry of Higher Education and Scientific Research and universities to use the (AI) technologies as an educational instrument to develop the system of Education in the Kurdistan Region.
Keywords: Artificial Intelligence (AI); Education System; Kurdistan Regional University; questionnaire